The clue in the crossword cipher - Keene, Carolyn (Keene, Carolyn. Nancy Drew mystery stories, 1993)
Lovely young Carla Ponce, who lives in Peru, invites Nancy and her friends Bess and George to visit her and solve her “monkey mystery,” which promises to lead to a fabulous treasure. A clue is carved on an intriguing wooden plaque that is so old, most of the crossword cipher is obliterated. When a notorious gang headed by El Gato (the Cat) steals the priceless relic, Nancy<U+2019>s hopes of solving the mystery are almost shattered. But the daring young detective<U+2019>s ability to think fast and act quickly results in the recovery of the plaque. Nancy<U+2019>s determined efforts to decode the crossword decipher take her to the magnificent, awe-inspiring Incan ruins at Cuzco and Machu Pichu. Through clever deductions, perseverance, and dangerous adventures, Nancy and her friends help to capture a ring of vicious smugglers and go on to make an astounding archaeological discovery.